1995
DOI: 10.1002/adv.1995.060140302
|View full text |Cite
|
Sign up to set email alerts
|

Weldlines in injection‐molded parts: A review

Abstract: It is a well-known fact that weldlines are unavoidable in most injection-molded products of even moderate complexity. While there are many situations where they are barely perceptible, weldlines represent a potential source of weakness in molded parts. In injection molding weldlines are generated when two separate melt streams join either in multigated molds or as a consequence of flow around obstacles. The development of many interesting materials has been hampered by poor weldline strength. Among such materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 60 publications
4
85
0
4
Order By: Relevance
“…It is generally believed that the weld line strength increases as the temperature and pressure at the weld increases. 118 Kim and Suh 119 studied the effect of mold temperature on the weld line strength. They showed that at elevated mold temperatures, the diffusion process at the weld line strengthens the weld line.…”
Section: Minimizing Weld Linesmentioning
confidence: 99%
“…It is generally believed that the weld line strength increases as the temperature and pressure at the weld increases. 118 Kim and Suh 119 studied the effect of mold temperature on the weld line strength. They showed that at elevated mold temperatures, the diffusion process at the weld line strengthens the weld line.…”
Section: Minimizing Weld Linesmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Shieu et al 38 examined the microstructure and tensile strength of the weld zone of PC/ABS blends prepared by two different welding techniques, i.e., hot plate welding and vibration welding. Fellahi et al 35,39,40 investigated the morphology and the tensile strength of weld-line specimens of nylon-6 and high-density polyethylene blend with and without an ionomer as a compatibilizer. Semba and Hamada 43 observed the etched samples of PC/ABS injection moldings using scanning electron microscopy and reported that a weld part with fine dispersion of ABS was found in the area below V-notch and the interface between the weld part and the part behind the weld part was the weakest part.…”
Section: Introductionmentioning
confidence: 99%
“…The weakness of welded regions for the homopolymer systems can be minimized by adjusting molding condition such as melt temperature. [25][26][27][28][29][30][31][32][33][34][35] In the case of polymer blends, together with the effect of processing conditions, the morphology at the weld line should be considered. The rheological properties of the blend components and the compatibilization are important factors that control the morphology of the dispersed phase at the weld line.…”
Section: Introductionmentioning
confidence: 99%
“…A análise do ângulo de junção dos fluxos pode determinar se irá existir uma linha de junção ou solda [2,3]. Vários pesquisadores têm empreendido esforços em estudos que abordam a redução da resistência devido à existência de linhas de soda e linhas de junção [4,5,6,7,8,9]. Na linha solda existe a difusão molecular entre as duas superfícies, pois quanto maior for a temperatura e o tempo de permanência na temperatura acima da T g maior será a difusão na interface [10,11,12].…”
Section: Introductionunclassified